Influencing the Post 2020 Global Biodiversity Framework (still interim due to COVID 19 pandemic) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
CCAFS coordinated development of policy brief on behalf of 11 CGIAR Centers, Treaty Secretariat, UNEP, for the February 2020 intergovernmental Working Group developing the Post 2020 Global Biodiversity framework. CCAFS staff followed-up making submissions in July 2020 on the draft monitoring approach. Negotiations are not yet finished. Meanwhile, the draft Post 2020 Framework and monitoring approaches substantially reflects some CCAFS-advocated positions. The document is still not ideal, but moving in the right direction. CCAFS will continue contributing in 2021.